Informatization of education as a means of increasing the effectiveness of the educational process - Hevko, Ihor (Journal of Education, Health and Sport, 2018)
The modern period of the development of society is characterized by a strong influence on it of information technologies that penetrate into all spheres of human activity and form a global information space. An inseparable and important part of these processes is informatization of education. Information technologies and education in the aggregate become those spheres of human interests and activities that mark the epoch of the XXI century and should become the basis for solving the problems facing humanity. In the information society, when information becomes the highest value, and the information culture of a person is the determining factor of professional activity, the requirements to the education system also change, and the status of education is significantly increased.